Haptics: Science, Technology, Applications 13th International Conference on Human Haptic Sensing and Touch Enabled Computer Applications, EuroHaptics 2022, Hamburg, Germany, May 22-25, 2022, Proceedings - Seifi, Hasti; Kappers, Astrid M. L.; Schneider, Oliver; Drewing, Knut; Pacchierotti, Claudio; Abbasimoshaei, Alireza; Huisman, Gijs; Kern, Thorsten A. (Lecture Notes in Computer Science, 2022)
This open access book constitutes the proceedings of the 13th International Conference on Human Haptic Sensing and Touch Enabled Computer Applications, EuroHaptics 2022, held in Hamburg, Germany, in May 2022. The 36 regular papers included in this book were carefully reviewed and selected from 129 submissions. They were organized in topical sections as follows: haptic science; haptic technology; and haptic applications.